2008
DOI: 10.1111/j.1365-2699.2008.01937.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytogeography of Solidago gigantea (Asteraceae) and its invasive ploidy level

Abstract: Aim  Newly formed polyploids experience problems of establishment and spread similar to those faced by newly introduced alien species. To understand the significance of polyploidy in biological invasions, we mapped the distribution of ploidy levels in Solidago gigantea Aiton in its native range in North America, and in Europe and East Asia where it is invasive. Location  North America, Europe and East Asia. Methods  Flow cytometry was used to measure ploidy levels in a total of 834 plants from 149 locations. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 54 publications
2
74
1
Order By: Relevance
“…This is in accordance with surveys that had been conducted by Fernald (1903) and Mulligan (1958) in eastern North America where only a few populations of L. ircutianum were found. The higher invasion success of the diploid L. vulgare is in contrast to studies that found a positive association between polyploidy and invasiveness in plants (Lafuma et al 2003;Kubátová et al 2008;Schlaepfer et al 2008;Treier et al 2009;Pandit et al 2011Pandit et al , 2014te Beest et al 2012). The higher abundance of L. vulgare in the introduced range could potentially be explained by differences in introduction pressure between the two species.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…This is in accordance with surveys that had been conducted by Fernald (1903) and Mulligan (1958) in eastern North America where only a few populations of L. ircutianum were found. The higher invasion success of the diploid L. vulgare is in contrast to studies that found a positive association between polyploidy and invasiveness in plants (Lafuma et al 2003;Kubátová et al 2008;Schlaepfer et al 2008;Treier et al 2009;Pandit et al 2011Pandit et al , 2014te Beest et al 2012). The higher abundance of L. vulgare in the introduced range could potentially be explained by differences in introduction pressure between the two species.…”
Section: Discussioncontrasting
confidence: 53%
“…Polyploidy has been found to be overrepresented in invasive plants (Pandit et al 2011(Pandit et al , 2014 and in various taxa with more than one ploidy level in the native range, only polyploids have become invasive (e.g. Lafuma et al 2003;Kubátová et al 2008;Schlaepfer et al 2008;Treier et al 2009). Furthermore, polyploids are expected to exhibit increased concentrations of secondary metabolites compared to their diploid progenitors and may therefore experience greater levels of herbivore resistance (Levin 1983;Dhawan and Lavania 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Another is that other ploidies had been also introduced, but they failed to establish or expand its ranges. Studies of the ploidy level of S. gigantea in the invasive and native range revealed that tetraploids were more invasive than diploids, and it was the only cytotype found in the invasive range (Schlaepfer et al 2008(Schlaepfer et al , 2010. Future research on population genetics and common garden experiments is necessary to evaluate the potential evolutionary dynamics of S. altissima after introduction.…”
Section: Resultsmentioning
confidence: 99%
“…This is an open question, but the many cases where both cytotypes occur in their native range but only polyploids do in the invasive ranges (Lafuma et al, 2003;Mandák et al, 2005;Kubátová et al, 2007;Schlaepfer et al, 2008;Treier et al, 2009) suggest a potential pre-adaptation of polyploids for invasiveness (te Beest et al, 2012). However, environmental stresses also increase the rate of unreduced gamete formation and thus of polyploidization events (Bretagnolle and Thompson, 1995;Ramsey and Schemske, 1998).…”
Section: The Long-term Gains Enhanced Invasiveness and Colonization Pmentioning
confidence: 99%